2022
DOI: 10.1002/jor.25437
|View full text |Cite
|
Sign up to set email alerts
|

Role of C‐reactive protein in the bone marrow of Modic type 1 changes

Abstract: Modic type 1 changes (MC1) are vertebral bone marrow lesions and associate with low back pain. Increased serum C-reactive protein (CRP) has inconsistently been associated with MC1. We aimed to provide evidence for a role of CRP in the tissue pathophysiology of MC1 bone marrow. From thirteen MC1 patients undergoing spinal fusion at MC1 levels, vertebral bone marrow aspirates from MC1 and intra-patient control bone marrow were taken. Bone marrow CRP, IL-1, and IL-6 were measured with enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…They found that increased CRP levels in MC BM correlated with blood CRP levels. 76 This supports previous reports of increased serum CRP in MC patients and pinpointed the MC lesion as the relevant area for elevated CRP levels. 77 CRP is an acute-phase protein, like SAP, also belonging to the pentraxin family of innate pattern recognition molecules.…”
Section: Evidence For Complement System Involvement In Dd and MCsupporting
confidence: 91%
See 3 more Smart Citations
“…They found that increased CRP levels in MC BM correlated with blood CRP levels. 76 This supports previous reports of increased serum CRP in MC patients and pinpointed the MC lesion as the relevant area for elevated CRP levels. 77 CRP is an acute-phase protein, like SAP, also belonging to the pentraxin family of innate pattern recognition molecules.…”
Section: Evidence For Complement System Involvement In Dd and MCsupporting
confidence: 91%
“…A further study assessed MC BM aspirates from patients undergoing spinal fusion surgery. They found that increased CRP levels in MC BM correlated with blood CRP levels 76 . This supports previous reports of increased serum CRP in MC patients and pinpointed the MC lesion as the relevant area for elevated CRP levels 77 .…”
Section: Evidence For Complement System Involvement In Dd and MCsupporting
confidence: 83%
See 2 more Smart Citations
“…Recent studies confirm the possibility that activated immune cells in MC1 bone marrow can lead to CEP damage 158 . Increased lactate dehydrogenase activity and increased concentration of C‐reactive protein and of complement factors in MC bone marrow indicate also a humoral immune response related to local tissue damage 125,159 . On a cellular level, CEP cells at MC levels express more tumor necrosis factor (TNF), a disintegrin and metalloproteinase with thrombospondin motifs‐5 (ADAMTS‐5), macrophage migration inhibitory factor (MIF), and its receptor CD74 124,160,161 .…”
Section: Importance Of Cep In Ivd Degenerationmentioning
confidence: 97%